Sistem Pengambilan Keputusan Pada Smp Islam Terpadu Al-Afkari - Nur Helmi; Fachruddin Fachruddin; Makmur Syukri (Peneliti.net, 2023)
In management or in educational institutions decision-making has a very important role, this is because the decisions taken by the principal in an educational institution are the result of final thoughts that should be carried out by his subordinates and people who have a relationship with the school institution he leads. The impact of mistakes in making decisions can be detrimental to schools, both from image loss to material/money losses. A decision making in an organization or school institution can have a big influence in a school. Therefore, at this time, research will be conducted on problem solving and decision making at SMP IT Al-Afkari so that the problem solving and decision making system implemented by the principal at the school can be understood. The purpose of this study is to be able to describe how the problem solving and decision making system is in SMP IT Al-Afkari. The type of research used by the author is qualitative research, with descriptive research methods. The decision-making system at Al-Afkari IT Middle School will be deliberated first if indeed this is indeed a decision to be taken that needs to be deliberated. Inhibiting factors for decision making at Al-Afkari IT Middle School apart from the teachers who are less active in deliberation activities for decision making there are also factors that greatly hinder the realization of decisions that have been set, namely the factor of financing